Integrated Thematic Oriented “Pop Up Book” Development on Thematic Learning for Lower Grade Elementary School - Rahayu, Sri; Hakim, Arief Rahman; Yuliana, Palupi Dwi; Ladamay, Iskandar (International Journal of Elementary Education, 2021)
The lack of use of learning media, especially in thematic learning, causes students to experience difficulties in learning. The need for learning media development in thematic learning to facilitate students in learning. This study aims to develop Pop-Up Book media and find the location and practicality of Pop-Up Book learning media based on integrative thematic learning on Theme 8 Safety at Home and Travel. This type of research is development. The research method used is the ADDIE model. This study consisted of expert validators of learning media, content expert validators, class teachers, and students. The data collection instruments used in this study were questionnaires and expert judgment. The data used in this study is a feasibility analysis and practicality analysis. The data analysis technique used is descriptive qualitative and quantitative analysis. The study results indicate that this learning media has gone through systematic stages of development research. Based on the validation of material experts, media experts, practitioners, and students, the Pop-Up Book's quality was very good. The Pop-Up Book learning media development is feasible, practical, and attractive to be used as a learning medium in Class 2 thematic learning. The Pop-Up Book media can facilitate students in learning so that it impacts increasing student learning outcomes.